Visiting Southern Forests: Architectural Imagery and Local Challenges in Huilo Huilo, Chile / Visitando Florestas do Sul: Imagens Arquitetônicas e Desafios Locais em Huilo Huilo, Chile - Alvarado, Rodrigo Garcia (2017)
ABSTRACTNatural reserve Huilo Huilo in the south of Chile is home to more than 80,000 hectares of temperate rainforest. After a long history of unregulated logging, since 1996, the area has been subject to a private conservation initiative. This includes tourist facilities with a unique architecture and variety of services, which have been recognized for promoting sustainable tourism, but are also facing various environmental and social challenges. This paper first reviews the context of national tourism, environmental development and sustainable construction, and then characterizes this reserve and the trajectory of interventions made therein. Subsequently, the building conditions and architectural configuration of the tourist resort and the visitor experience are examined. Various academic and public questions raised by the installation are explored, in particular regarding the conservation of the forest, the participation of local people, energy supply and consumption, and social segmentation, as well as the symbolism of Huilo Huilo´s architecture, spatial planning and building technology. Finally, the relationship between natural conservation and tourism management are discussed and the barriers and opportunities that these entail are examined.KEYWORDSEcotourism. Nature Conservation. Local development. Natural Reserve Huilo Huilo, Chile. RESUMOA reserva natural Huilo Huilo, no sul do Chile, abriga mais de 80 mil hectares de floresta temperada. Após uma longa história de exploração não regulamentada, desde 1996 a área está sujeita a uma iniciativa privada de conservação. Isso inclui instalações turísticas com arquitetura única e uma variedade de serviços, reconhecidos por promoverem um turismo sustentável, mas enfrentam vários desafios ambientais e sociais. Este artigo analisa, primeiro, o contexto do turismo nacional no Chile, o desenvolvimento ambiental e construção sustentável, caracteriza a reserva e a trajetória das intervenções nela realizadas. Posteriormente, são examinadas as condições de construção e configuração arquitetônica da estância turística e a experiência do visitante. Várias questões acadêmicas e públicas levantadas pela instalação são apresentadas, em particular no que se refere à conservação da floresta, à participação da população local, ao fornecimento e ao consumo de energia e à segmentação social, bem como o simbolismo da arquitetura de Huilo Huilo, o ordenamento do território e tecnologia de construção. Finalmente, é discutida a relação entre a conservação natural e a gestão do turismo e examinam-se as barreiras e as oportunidades que isso implica.PALAVRAS-CHAVEEcoturismo. Conservação da Natureza. Desenvolvimento Local. Reserva Natural Huilo Huilo, Chile. AUTORESRodrigo Garcia-Alvarado – Doutor. Professor no Departamento de Diseño y Teoría de la Arquitectura, Universidad del Bío-Bío, Concepción, Chile. Currículo: https://www.researchgate.net/profile/Rodrigo_Garcia_Alvarado. E-mail: rgarcia@ubiobio.clMaureen Trebilcock Kelly - Doutor. Professor no Departamento de Diseño y Teoría de la Arquitectura, Universidad del Bío-Bío, Concepción, Chile. Currículo: https://www.researchgate.net/profile/Maureen_Trebilcock/publications?pubType=article. E-mail: mtrebilc@ubiobio.clHernan Ascui Fernandez – Mestre. Doutor. Professor no Departamento de Diseño y Teoría de la Arquitectura, Universidad del Bío-Bío, Concepción, Chile. Currículo: http://www.farcodi.ubiobio.cl/index.php/hernan-ascui/.  E-mail: hascui@ubiobio.cl REFERENCES Brundtland Commission (1987). Report of the World Commission on Environment and Development. Washington: United Nations.World Tourism Organization (2002). World Ecotourism Summit – Final Report, Madrid: World Tourism Organization and the United Nations Environment Programme.Elbers, J. (2011). Las áreas protegidas de América Latina Situación actual y perspectivas para el futuro. México: Ministerio de Medio Ambiente y Medio Rural y Marino.Drumm A., Moore A., Soles A., Patterson C. & Terborgh J. (2004) Ecotourism Development, A Manual for Conservation Planners and Managers,  2. The Business of Ecotourism, Development and Management. Arlington: The Nature Conservancy.Levine D., Berenson M. & Krehbiel T. (2006). Estadística para administración. México: Pearson.Roman, B. & Nahuelhual L. (2009). Áreas protegidas públicas y privadas en el sur de Chile: caracterización del perfil de sus visitantes, Estudios y Perspectivas en Turismo 18(4), 490-507.Petermann, V. ed. (2011) Huilo-Huilo: la reserva biológica del sur del mundo: construyendo un sueño Panguipulli: Hoteles Huilo-Huilo. Panguipulli: Fundación Huilo Huilo.World Travel and Tourism Council (2014). Travel and Tourism Economic Impact 2014. London: World Harlequin Building.Sernatur (2015). Anuario de Turismo 2014. Santiago: Servicio Nacional de Turismo, Gobierno de Chile.Núñez- Ávila M., E. Corcuera, A. Farías, P. Pliscoff, J. Palma, M. Barrientos & C. Sepúlveda. (2013). Diagnóstico y Caracterización de Iniciativas de Conservación Privada en Chile. Santiago: Fundación Senda Darwin.Teillier, S., Macaya-Berti, J., Bonnemaison C., Delaunoy, J. & Marticorena A. (2013). A contribution to the knowledge of the flora of Huilo Huilo Biological Reserve, Región de Los Ríos, Chile. Gayana Botanica 70(2), 194-234.Navarro J. & Corcuera E. (2002). Reserva Biologica Huilo Huilo: Desarrollo económico, conservación e integración humana. Revista Ambiente y Desarrollo, 18(2,34), 132-136.Fundación Huilo-Huilo. (2009). Memoria Fundación Huilo-Huilo. Panguipulli: Fundación Huilo-Huilo.Red de Organizaciones Ambientales de Panguipulli. (2013). Informe Complementario, Proyectos Central Hidroeléctrica Neltume y Línea de Alta, Tensión S/E Neltume - Pullinque de Endesa Enel, Panguipulli: Comunidades Mapuche Lago Neltume, Parlamento Mapuche de Koz Koz, Fundación Huilo Huilo.Municipalidad de Panguipulli. (2014) .Acta N°15 del 13 de Mayo del 2014, Sesión Ordinaria de Concejo Municipal. Panguipulli: Municipalidad de Panguipulli.Tiffin, S., Torres, X. & Neira, F. (2008). Actividades ecoturísticas y clusters en Chile. Estudios y Perspectivas en Turismo, 17(4), 315-335.Roldban, J. (1993) The Financing Requirements of Nature and Heritage Tourism in the Caribbean, Washington: Dept. of Regional Development and Environment, Organization of American States. Recebido: 7 MAI 2017Avaliado: MAIAceito: 26 JUN 2017